(untitled) (Global Journal of Science Frontier Research, 2022)
The study was conducted in twenty open defecation free communities of the Mion District in the Northern Region with the objective of assessing the determinants of open defecation free communities based socio-demographic and economic status of household heads correlational analysis. The study design was mainly quantitative and involved225 respondents. The study found that, 73.4 percent have hand washing facilities for washing their hands after defecating but no soap, 62.2 percent of the respondents indicated had hand washing facilities, water and soap. The correlation analysis shows that there was a relationship between household size and open defecation free communities (p=0.000), age of respondents and open defecation free communities (p=0.000), religion and open defecation free communities (p=0.000) and the presence of water at toilets and open defecation free communities (p=0.017).